(untitled) (Construction Economics and Building, 2012)
Capitalising useful knowledge for construction procurementselection (CPS) decisions would provide a valuable asset to clientorganisations, as the successful/unsuccessful experience wouldhelp decision-makers avoid the occurrence of similar errors andensure the most suitable procurement system is employed fora construction project. As a result, there is a need to examinethe potential for developing a knowledge management model tocapture and reuse experiential knowledge to guide CPS decisions.This paper begins by identifying a suitable approach for managingCPS knowledge. This is followed by a discussion of the knowledgerequired for CPS decision support. A prototype knowledgemanagementmodel is developed, using the case-based reasoning(CBR) approach, and a mechanism for the retrieval and reuse ofknowledge for guiding CPS decisions is elucidated. The resultsindicate that CBR is a suitable tool for formulating the procurementselection parameters and selecting a suitable procurementsystem for a construction project. This is primarily becausethe CBR approach is flexible enough to allow closely matchinghistoric cases to be retrieved as well as enabling the decisionmakerto adapt the proposed solution based on the predominantcharacteristics of the client, project and external environmentpertinent to the current project.